Experiment and measurement with high-energy helium irradiation to tungsten using tandem accelerator for divertor in magnetic confinement fusion system. (December 2017) - Uchida, Yuki; Saito, Seiki; Saito, Nobuo; Suzuki, Tsuneo; Takahashi, Kazumasa; Sasaki, Toru; kikuchi, Takashi; Harada, Nob.
Abstract: An experimental system for irradiating high-energy (4 MeV) helium beam was developed to investigate irradiation damage of tungsten by using tandem accelerator. In this system, particle fluence to a tungsten thin plate was achieved to 10 22 ions/m 2 . Electron diffraction images were acquired for damaged tungsten using a transmission electron microscope (TEM) to measure the particle loading by helium irradiation. Crystal structure was qualitatively changed between helium irradiated area and non-irradiated area from diffraction patterns.